2010
DOI: 10.1007/s12237-009-9262-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoreline Modifications on Supratidal Macroinvertebrate Fauna on Puget Sound, Washington Beaches

Abstract: In coastal environments, the supratidal zone bridges marine and terrestrial ecosystems and is important for energy exchange. However, it is also subject to extensive anthropogenic disturbance, such as armoring of shorelines. Shoreline armoring is extensive along many coasts, but the impacts on biota are comparatively unknown. Between 2000 and 2002, paired and synoptic sampling regimes were employed to assess armoring effects on insects and benthic macroinvertebrates in the supratidal zone of Puget Sound beache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…A study along an estuary at the Campbell River in BC, Canada, also documented observations of juvenile salmonids darting to the surface to feed (MacDonald et al, 1987), further showing the importance of surface-feeding at various points in the estuary. Other studies have shown insects to be significantly reduced on armored shorelines where vegetation was removed (Romanuk and Levings, 2003;Sobocinski et al, 2010), and continued development of the vegetation communities may increase the input of insects and feeding opportunities for juvenile salmon.…”
Section: Invertebratesmentioning
confidence: 98%
See 1 more Smart Citation
“…A study along an estuary at the Campbell River in BC, Canada, also documented observations of juvenile salmonids darting to the surface to feed (MacDonald et al, 1987), further showing the importance of surface-feeding at various points in the estuary. Other studies have shown insects to be significantly reduced on armored shorelines where vegetation was removed (Romanuk and Levings, 2003;Sobocinski et al, 2010), and continued development of the vegetation communities may increase the input of insects and feeding opportunities for juvenile salmon.…”
Section: Invertebratesmentioning
confidence: 98%
“…For example, fish assemblages have been found to differ due to environmental variables of habitat types in the west coast of Australia (Valesini et al, 2004), Chesapeake Bay, USA (Bilkovic and Roggero, 2008), and Puget Sound, USA (Toft et al, 2007). Shoreline armoring can negatively impact fish prey such as terrestrial insects (Toft et al, 2007) and aquatic invertebrates to varying degrees, depending on how low in tidal elevation the armoring encroaches (Peterson et al, 2000;Chapman, 2003;Cruz Motta et al, 2003;Romanuk and Levings, 2003;Moschella et al, 2005;Sobocinski et al, 2010). These types of impacts can limit the opportunity for shoreline-oriented fishes such as juvenile salmon to feed and benefit from a site (Simenstad and Cordell, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other shoreline types, wetlands provide larger amounts of allochthonous carbon to adjacent nearshore waters (Weinstein et al 2005), support greater densities of infaunal and epifaunal invertebrates (King et al 2005;Seitz et al 2006), and are associated with more subtidal benthic structure (e.g., woody debris, shellfish beds) that may serve as habitat (Bilkovic & Roggero 2008). Similarly, natural beaches have more organic material and greater density and diversity of benthic invertebrates than armored beaches (Sobocinski et al 2010), and beach alteration can negatively impact nursery areas (Peterson & Bishop 2005). Munsch et al (2015b) also found reduced epibenthic prey in the water column at hardened shorelines when compared to beaches, which in turn affected the diets of some fish.…”
Section: Local-scale Effects Of Shoreline Typementioning
confidence: 99%
“…In developed areas, this tendency places the juvenile salmon close to shoreline modifications (Toft et al 2007), including armoring that reduces the production of their invertebrate prey (Sobocinski et al 2010). Juvenile salmon are active visual predators, capturing individual prey in the water column and from the substrate (Quinn 2005).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%